PARAMETRIC STUDY ON MECHANICAL DESIGN OF VORTEX BLADELESS - Jason Teguh, Bradley
Wind energy is one of the renewable energy sources. The wind energy potential in Indonesia in 2017 was estimated at 60,647 megawatts with a potential wind range between 3 m/s and more than 5 m/s. The higher wind speed happens because mountains surround Indonesia’s geographical area, increasing the wind speed by the nozzle effect. However, Indonesia consists of various islands, and transporting and installing wind turbines is complicated and expensive. Therefore, a new type of wind turbine or wind energy will be discussed in this paper. In this thesis, the mechanical design of a vortex bladeless wind turbine will analyze. Vortex bladeless wind turbine generated energy from vortex-induced vibration, producing an amplitude to vibrate and convert to electrical. The method that the author will use is by using computational fluid dynamics (CFD) and the help of SolidWorks to design the shape. To validate the simulation result, a reliable paper will confirm the simulation with an error of less than 10%. From there, the author will analyze the change of mast shape such as cylindrical or conical, even oval; also, author believes there should be a correlation of height and diameter of the mast. The result from the simulation will be analyzed to help other researcher studies that other papers have not provided.